Total immunoglobulin G and IgG1 subclass levels specific for the MSP-119 of Plasmodium falciparum are different in individuals with either processing-inhibitory, blocking or neutral antibodies (2010)
Background: Some MSP-119 specific antibodies that inhibit merozoite invasion also inhibit the secondary processing of MSP-1. However the binding of these inhibitory antibodies can be blocked by another group of antibodies, called blocking antibodies, which recognize adjacent or overlapping epitopes, but themselves have no effect on either MSP-1 processing or merozoite invasion. These antibodies have been reported to be present in individuals living in a malaria endemic area. Methods: Blood samples were obtained from children shown to have processing inhibitory, blocking, and neutral antibodies in a previous study. Enzyme linked immunosorbent assay (ELISA), was used to determine the total IgG, IgM and IgG subtypes. Results: There was a significant difference in anti-MSP-119 IgG, while there was no significant difference in the anti-MSP-119 IgM. Only anti MSP-119 IgG1, amongst the IgG subtypes was significantly different between the groups. Conclusion: This study shows that antibodies against MSP-1 are different not only in specificity and function but also in the amount of total IgG and IgG subtype produced.